Recent developments in social and environmental accounting research - Eugénio, T.; Costa Lourenço, I.; Morais, A. I. (Social Responsibility Journal, 2010)
Purpose – The last years have witnessed a growth in interest in social and environmental questions. Many companies have developed environmental management and auditing systems and altered their social and environmental disclosure practices. These developments resulted in the growth of research focusing on the analysis of information disclosed by companies. The purpose of this study is to contribute a reflection on the papers that have been published on social and environmental accounting from 2000 to 2006. Design/methodology/approach A literature review of the papers examining social and environmental matters published in selected accounting journals allows the identification of the key content issues, methodologies and research questions which have been predominant in the social environmental accounting research (SEAR) area. It also enables one to pin?point areas for future research. Findings The content was examined and classified in four groups: social and environmental accounting systems; social and environmental disclosures; regulation impact; and relations among environmental disclosure and environmental performance. For each group, the research method; data origins and type of data; industry and country were identified. Almost all the studies are based on content analysis and interviews. Data are collected not only from the financial statements but also from other types of information disclosed by companies. In many cases, industry activities are selected carefully and most of the studies used data from the UK, Australia, and the USA. Originality/value The paper provides a contribution to the development of the SEAR area, exploring different views. It also helps schools to identify areas for future research.